Is Per Capita Real GDP Stationary in G-7 Countries? New Evidence from A Fourier Panel Unit Root Test - Tunahan Hacıimamoğlu (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The stability of macroeconomic variables and whether the impact of a shock on these variables is permanent or temporary is important for policy-makers and researchers. As an indicator of growth and prosperity, gross domestic product (GDP) is among the important macroeconomic variables. After all, due to the advantages of current panel data analysis techniques over conventional methods, it is important to use the aforementioned methods in analyzing the existence of unit-root for GDP. Accordingly, the aim of this study is to investigate whether per capita real GDP in G-7 countries followed a stationary process between 1970-2019 with a stronger unit-root test (BCIPS) that takes into consideration cross-section dependence, multi-factor structure, and structural changes. Empirical results reveal that per capita real GDP for G-7 countries has a stationary structure. In this context, it has been determined that the impact of a shock on per capita real GDP is temporary in G-7 countries, therefore, by means of monetary or fiscal policy instruments, it is not necessary to intervene in fluctuations occurring the output level.